The Role of Communication Technology in Building Social Interaction and Increasing Digital Literacy in Ibu Sibuk Community - Juan Prince Adeliant; Tangguh Okta Wibowo; Andiani Fitri Febrina; Chelsea Roxanne; Gabriella Christie Kartadibrata; Khairul Syafuddin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Digital transformation involves deep changes in businesses and organizations, with maximizing changes and opportunities in technology and social impact as top priorities. Further research was conducted to analyze the effects of digital transformation on communication in communities and identify effective strategies to overcome communication breakdowns arising from technological change. This research discusses the important role of communication technology in a community, namely the IbuSibuk community. The method used is a case study, with the data collection technique being structured interviews. The results showed that the use of communication technology has a significant role in facilitating social interaction, information exchange, and the self-development of members in the IbuSibuk Community. Platforms such as Instagram, WhatsApp, and Telegram allow members to share information, ideas, and support, while identity as a member of IbuSibuk provides additional benefits, such as the opportunity to collaborate with brands or companies. There are some technical barriers and a lack of digital literacy that affect the use of technology in the community. Therefore, efforts are needed to improve digital literacy so that all members can utilize technology effectively and participate actively in the community. Improving digital literacy includes aspects of digital ethics, digital culture, and digital safety. Support and education on the use of technology can be organized through external initiatives as well as internal activities within the IbuSibuk community